2007
DOI: 10.1016/j.surfcoat.2006.11.040
|View full text |Cite
|
Sign up to set email alerts
|

The surfactant addition effect in the elaboration of electrodepositated NiP-SiC composite coatings

Abstract: International audienceIn this work, NiP-SiC composite coatings were prepared by electrodeposition from a plating bath containing NiSO4*6H2O; NiCl2*6H2O; H3PO3; H3PO4; Na2 SO4 and SiC particles (average diameter of 600 nm) in suspension. Anionic surfactant (SDS -- sodium dodecyl sulfate, CH3 (CH2)11SO4Na) or cationic surfactant (CTAHS--cetyltrimethylammonium hidrogensulfate, C19H43NO4S) were also added to this suspension. The number of incorporated particles by area unit (αnp/A) was evaluated by image analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 19 publications
5
30
0
Order By: Relevance
“…2a-c). This phenomenon, also observed by other authors in similar systems [11,20,25,[35][36][37], may be based upon the probability of mechanical interaction between the cathode and the suspended particles. The particle is completely incorporated into the metallic matrix only when the deposit reaches a certain thickness, so that the ejection, caused by the arriving particles, is restrained.…”
Section: Coating Processsupporting
confidence: 78%
“…2a-c). This phenomenon, also observed by other authors in similar systems [11,20,25,[35][36][37], may be based upon the probability of mechanical interaction between the cathode and the suspended particles. The particle is completely incorporated into the metallic matrix only when the deposit reaches a certain thickness, so that the ejection, caused by the arriving particles, is restrained.…”
Section: Coating Processsupporting
confidence: 78%
“…Various additives have been studied to reduce the agglomeration of particles [30], increasing the volume fraction of SiC particles in the deposit, good dispersion and high hardness. In general, cationic and anionic surfactants are being used to change the surface characteristics of the particles [12,[30][31][32][33][34][35][36][37][38][39][40][41]. Saccharine has been used by Zimmerman et al and Lei Shi et al [22,42].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, applications and requirements investigations have been carried out with the aim of improving specific aspects of the product or the process. Recently, some researchers showed that adding surfactant in the bath improves the coating morphology and other properties of the coating [9][10][11]. Surfactants are surface active agents that lower the surface tension of a liquid, allowing easier spreading and lower the interfacial tension between two liquids.…”
Section: Introductionmentioning
confidence: 99%